Water mite (Acari, Hydrachnidia) Fauna of Adıyaman Province - Beyaz, Seda; Esen, Yunus; Erman, Orhan (Fırat University, 2016)
In this study, it has been evaluated water mite species collected from Adıyaman province in 2013 and 2014 years. Totally, it has been identified 60 species belonging to 15 families.Of these, Lebertia (s. str.) cognata Koenike, 1902 and Atractides (s. str.) gomerae Lundblad, 1962 are new records for the Turkish fauna.All of the identified species, except Arrenurus (s. str.) cuspidifer Piersig, 1894, are newly recorded from Adıyaman province. L. cognata and A. gomerae are reviewed the morphological features and distribution in the World. Moreover, Lebertia (s. str.) marasensis Esen & Erman, 2015, Hygrobates (s. str.) anatolicus Peši? & Esen, 2013, Arrenurus (s. str.) ovatipetiolatus Esen & Erman, 2013 that are endemics for Turkey with Brachypoda (Hemibrachypoda) orientalis Peši? & Esen, 2013 that is known only from Turkey and the Caucasus have been also collected from Adıyaman Province

Bu çalışmada, 2013-2014 yıllarında Adıyaman’dan toplanan su keneleri değerlendirilmiş ve toplam 15 familyaya ait 60 tür tespit edilmiştir. Bu türlerden; Lebertia (s. str.) cognata Koenike, 1902 ve Atractides (s. str.) gomerae Lundblad, 1962 Türkiye faunası için yeni kayıttır. Arrenurus (s. str.) cuspidifer Piersig, 1894 hariç tespit edilen türlerin tümü Adıyaman ilinden ilk defa kaydedilmiştir. L. cognata and A. gomerae’nin morfolojik özellikleri örneklerimiz üzerinden gözden geçirilmiş ve dünyadaki yayılışları verilmiştir. Ayrıca, Türkiye için endemik olan, Lebertia (s. str.) marasensis Esen & Erman, 2015, Hygrobates (s. str.) anatolicus Peši? & Esen, 2013, Arrenurus (s. str.) ovatipetiolatus Esen & Erman, 2013 ile Kafkaslar ve Türkiye’den bilinen Brachypoda (Hemibrachypoda) orientalis Peši? & Esen, 2013 Adıyaman’dan da yakalanmıştır
Adıyaman İli Su Kenesi (Acari, Hydrachnidia) Faunası